Exploring the relationship between the level of facial nerve injury and surgical outcome: Application of a new anatomical classification system in a limited cohort undergoing marginal mandibular nerve reconstruction - Villiam Vejbrink Kildal; Alex Okello Wamalwa; Ludvig Tidehag Walan; Andrés Rodriguez-Lorenzo (JPRAS Open)
Background: Reconstruction of the marginal mandibular nerve (MMN) is important for achieving optimal outcomes in the treatment of facial paralysis. However, the heterogeneity of injuries, ranging from extensive proximal facial nerve injuries to isolated distal MMN injuries, complicates meaningful outcome comparisons. This study assessed a new anatomical classification system for stratifying facial nerve injuries by injury location. The aim was to study MMN outcomes in proximal versus distal injuries and determine whether this system could provide a more reliable way to compare surgical results. Methods: A retrospective, single-center study of MMN reconstructions (either independent MMN reconstructions or as part of a broader facial nerve reconstruction) was conducted over a 12-year period. Clinical outcomes were assessed using a classification system for facial nerve injuries (Levels 1−3, based on facial nerve injury location: Level 1 = proximal, Level 2 = parotid area, Level 3 = distal). Outcome measures included the Terzis' Lower Lip Grading Scale, photogrammetry, Sunnybrook, and quality-of-life assessments (Facial Disability Index, Facial Clinimetric Evaluation Scale). Results: Sixteen patients (7 female; mean age 46.5 ± 20.6 years) underwent MMN reconstruction. Across all outcome measures, distal Level 3 injuries yielded the best outcomes, followed by Level 2, with proximal Level 1 injuries showing the least favourable results. Conclusions: Proximal facial nerve injuries demonstrated inferior MMN outcomes compared with distal injuries, highlighting the importance of considering injury location when comparing results. The proposed classification system may provide a practical method for grouping patients according to anatomical injury location, enabling more meaningful and standardized comparisons of surgical outcomes among patients with similar characteristics and treatment protocols.